Analysis of Cases of Manipulation of Financial Statements and Violations of the Code of Ethics of The Accounting Profession - Arini, Wirna Sofi; Trisnaningsih, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the manipulation of financial statements and violations of the accountant code of ethics by PT. Adisarana Wanaartha Life (PT AWL). Using a case study approach, the research provides an in-depth analysis of these issues. Findings reveal that PT AWL manipulated financial reports, while its partner, KAP KNMT (a public accounting firm), failed to detect these irregularities. Both PT AWL and KAP KNMT violated ethical principles, including integrity, objectivity, competence, confidentiality, and professional behavior, as they passed audits without identifying errors. Consequently, administrative sanctions, fines, and business license revocations were imposed, with PT AWL's assets of Rp 2.4 trillion confiscated in October 2022.